Os cursos de especialização para formação docente do PROEJA: a tecitura da oferta e dos resultados na percepção de cursistas da região sul do Brasil - Maron, Neura Maria Weber (2013)
Integrating the policy of the Integration Program of Professional education and basic education for Adult and Young People – PROEJA, in June 2006 SETEC/MEC started to promote Teacher education through Specialization Courses for PROEJA teachers. This thesis analyzes the offer and the results of the first three editions of this course offered in southern Brazil at the perception of course participants. The research’s goal was to verify how the curriculum’s organization of the specialization course allowed the docent participants to assimilate ideas, concepts and principles of PROEJA, such as: comprehension of initial and continuing formation; comprehension of integration and work as an educational principle; the concept of researcher teacher. The policy was analyzed in its contradictory aspect by the hypothesis that if, on one hand there was the certification of a large number of PROEJA’s specialist teachers, on the other hand, this course did not break with the practice of a pragmatic, occasional, precarious, fragile and superficial formation that historically characterized the teachers’ formation to act on the education for Adult and Young people and on EPT in Brazil. To understand the policy of PROEJA’s teacher formation, the Base Document and the PROEJA’s Specialization Course Proposal were analyzed, both developed by SETEC/MEC. To study the offer of PROEJA’s specialization courses, were analyzed the Opening Classes Edicts, the Courses’ Pedagogical Projects, and the three poles Detailed Reports. For the analysis of the study’s results, were interviewed two professional coursing teachers participants from each of the nineteen cities/campi who offered such training in southern Brazil. The data analysis showed that the teacher formation was pragmatic and instrumental, because of its binding to another specific educational program; it was occasional because of its discontinuous offer; it was an precarious offer due its load extension, overload and work journey intensification for the teachers; and due its selection process in which prevailed the exclusionary selection criteria; it was superficial due the marginal importance given by the PROEJA’s Base Document; it was fragile because of the inconsistency among curricular units, axes, goals and principles in PPP courses, due the lack of connection between theory and practice in the course, and due the fragmentation of the programmatic contents of the curricular axes, which misread the proposal and determined a superficial formation about the concepts and conceptions of PROEJA, compromising the results of this formation. On this way, we confirmed the hypothesis of the research. Contradictorily, the formation had the merit of bringing together teachers from two modalities of basic education, historically marked by gaps and precariousness of initial specific formation; the production of monographies contributed to the improvement of the subject; it allowed to enlarge the coursing teacher’s understanding about the public of EJA/PROEJA; and boosted the ulterior formation with the continuity of studies of many teachers in Master’s and Doctoral Programs.